Government Responsibility in The Management of Natural Resources for The Protection of Economic, Social, and Cultural Rights in The Balaesang Region - Saly, Jeane Neltje; APHA, Journal Manager (Jurnal Hukum Adat Indonesia, 2017)
There are two aims of this paper: first to analyze the responsibility of the government in the commitment to protect the rights of indigenous and tribal peoples in natural resource management activities; secondly, to analyze the implementation of government responsibilities in mining management in relation to the rights of indigenous and tribal peoples in enjoying their rights in the ecosystem, such as the environment. The method used in the research is empirical normative method, namely research that emphasizes the secondary data that is by studying and reviewing the principles of law and positive law principles derived from the existing literature materials in legislation and the provisions especially in relation to the exclusion of indigenous people's rights in the obligation of the state to create a healthy environment for the management of natural resources as a manifestation of human rights protection, and supplemented by empirical data in the form of interviews with related parties in Balaesang Tanjung Donggala District. The results show that natural resource management activities, linked to indigenous and tribal peoples' rights in environmental protection are regulated in various laws, both nationally and internationally. Implementation of government responsibility in mining management is related to the right of customary law community in enjoying the environment has not been optimally done. From the case of Balaesang Tanjung Donggala, it is envisaged that local governments ignore the rights of indigenous and tribal peoples in enjoying a healthy environment.